Characterization of 13 polymorphic microsatellite loci in Rimicaris hybisae, a shrimp from deep-sea hydrothermal vents - Jacobson, A; Plouviez, S; Thaler, A D; Van Dover, C L (Conservation Genetics Resources, 2013)
Rimicaris hybisae is a deep-sea alvinocaridid shrimp found at hydrothermal vents along the Mid-Cayman Spreading Center. Eleven selectively neutral and unlinked polymorphic microsatellite loci were developed for this species and two additional loci were found to cross-amplify from a related species. Nine loci conformed to Hardy-Weinberg expectations. Seven loci cross-amplified with Chorocaris sp. 2, an alvinocaridid shrimp found at vents in the Southwestern Pacific. Microsatellite loci developed for R. hybisae are being deployed to study connectivity and genetic variability of populations along the Mid-Cayman Spreading Center.
Keywords: ROV Jason (Remotely Operated Vehicle)